An ELM-based single input rule module and its application in power generation - Chong Tak Yaw; Shen Young Wong; Keem Sian Yap (Institute of Advanced Engineering and Science, 2020)
Extreme Learning Machine (ELM) is widely known as an effective learning algorithm than the conventional learning methods from the point of learning speed as well as generalization. In traditional fuzzy inference method which was the